Autoregulation of simian virus 40 gene A by T antigen. - Reed, S I (1976)
During lytic infection by simian virus 40, gene A is transcribed into early RNA, which is translated into A protein (T antigen). Both the rate of synthesis and the intracellular amount of early RNA are higher in cells infected by temperature-sensitive A (tsA) mutants than in cells infected by wild-type virus. These differences are observed at permissive temperature (32 degrees) and are amplified greatly after a shift to restrictive temperature (41 degrees). For example, at 32 degrees cells infected by tsA mutants synthesize early RNA approximately twice as fast as cells infected by wild-type virus. After the shift to 41 degrees, the rate of synthesis in the tsA infection increases to 15 times the rate in the wild-type infection. In contrast, cells infected by tsA mutants do not overproduce late RNA. We suggest that the A protein regulates its own synthesis by negative feedback control of gene A transcription.